Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/cam4.2055
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarker panels for the diagnosis of gastric cancer

Abstract: Gastric cancer is a leading cause of mortality due to neoplastic disease. Although early detection of gastric cancers can decrease the mortality rate, it remains a diagnostic challenge because of the lack of effective biomarkers. In this study, fifteen gastric cancer patients and ten healthy subjects were recruited to assess novel serum biomarkers for gastric cancer using antibody microarray technology. ELISA was utilized to validate the antibody array results. As a result, compared to the controls, eleven cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 35 publications
0
63
0
3
Order By: Relevance
“…GHR was recently reported to mediate cell progression and apoptosis via the BRAF/MEK/ERK signaling pathway in breast cancer (26). According to the literature, GHR was elevated in GC serum samples and high expression of GHR mRNA was associated with a poor outcome in GC patients (27,28), which suggested that GHR may serve as novel biomarkers for the early diagnosis and prognosis determination of GC.…”
Section: Discussionmentioning
confidence: 99%
“…GHR was recently reported to mediate cell progression and apoptosis via the BRAF/MEK/ERK signaling pathway in breast cancer (26). According to the literature, GHR was elevated in GC serum samples and high expression of GHR mRNA was associated with a poor outcome in GC patients (27,28), which suggested that GHR may serve as novel biomarkers for the early diagnosis and prognosis determination of GC.…”
Section: Discussionmentioning
confidence: 99%
“…Great efforts have been made to the diagnose and treat this disease; however, the mortality rate has remained essentially unchanged worldwide in the past decades (3). Currently, clinicians extensively use diagnostic and prognostic biomarkers to improve the clinical course of GC (4,5). However, gastric carcinoma involves mixed cell types with variable degrees of differentiation, and the majority of serum biomarkers have low sensitivity and low positive predictive value, such as CEA, CA19-9 and CA72-4 (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The poor prognosis could be because most people were diagnosed with advanced disease. Identification of new biomarkers and potential mechanisms are urgent to improve prognosis of DGC [4].…”
Section: Introductionmentioning
confidence: 99%